Bibliometric Analysis of Social Media Trends in Hospital Marketing - Ekawati, Dian (Advances In Social Humanities Research, 2025)
This study presents a bibliometric analysis of social media trends in hospital marketing over the past decade, highlighting key developments and emerging themes within this field. The increasing integration of social media into hospital marketing strategies has revolutionized patient engagement, service promotion, and brand management. Utilizing data from major academic databases from Scopus, this research employs a sequential explanatory design, combining quantitative bibliometric analysis with qualitative insights to examine publication trends, citation patterns, and co-authorship networks. The findings reveal distinct phases of research activity, with a significant surge in publications around 2019, driven by advancements in digital marketing. Notably, the United States emerges as the central hub of international collaboration, with strong ties to countries such as Canada, the United Kingdom, and Australia. Key themes identified include the impact of social media on patient satisfaction, the role of specific platforms like Facebook and Twitter, and the evolving nature of hospital branding. This analysis provides a comprehensive overview of the intellectual structure of the field, offering valuable insights for future research and practical applications in hospital marketing using another social media platform for example: Instagram or Twitter (X).